Brodie vs Hummers graphite oxides for preparation of multi-layered materials. (May 2017) - Talyzin, Alexandr V.; Mercier, Guillaume; Klechikov, Alexey; Hedenström, Mattias; Johnels, Dan; Wei, Di; Cotton, Darryl; Opitz, Andreas; Moons, Ellen
Abstract: Graphite oxides synthesized by one and two step Brodie oxidation (BGO) and Hummers (HGO) methods were analyzed by a variety of characterization methods in order to evaluate the reasons behind the difference in their properties. It is found that the Brodie method results in a higher relative amount of hydroxyl groups and a more homogeneous overall distribution of functional groups over the planar surface of the graphene oxide flakes. The higher number of carbonyl and carboxyl groups in HGO, detected by several methods, including XPS, NMR and FTIR, unavoidably results in defects of the graphene "skeleton", holes and overall disruption of the carbon-carbon bond network, stronger deviation from planar flake shape and poor ordering of the graphene oxide layers. It is also suggested that functional groups in HGO are less homogeneously distributed over the flake surface, forming some nanometer-sized graphene areas. The presence of differently oxidized areas on the GO surface results in inhomogeneous solvation and hydration of HGO and effects of inter- and intra-stratification. The proposed interpretation of the data explains the higher mechanical strength of multi-layered BGO membranes/papers, which are also less affected by humidity changes, thus providing an example of a membrane property superior to that of HGO. Graphical abstract: